Review paperAcne inversa: difficulties in diagnostics and therapy - Bergler-Czop, Beata; Hadasik, Karolina; Brzezińska-Wcisło, Ligia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Acne inversa (hidradenitis suppurativa) is a potentially severe and chronic inflammatory disease with a significant negative influence on the quality of life. Usually, lesions are located in the areas of skin folds and it is characterized by the presence of painful nodules and fistulas with a tendency to tissue fibrosis. Currently, it is suggested that follicular occlusion by infundibular hyperkeratosis plays a crucial role in pathogenesis and an occupation of apocrine sweat glands is a secondary phenomenon. Most often, it refers to men after puberty. This article tries to present the latest theory concerning the etiology of inverted acne and methods of its treatment. It also describes the most common errors in diagnostic and therapeutic procedures, which are mainly connected with repeated and long antibiotic therapy and not radical surgical treatment.